Perencanaan Strategis Sistem Informasi Menggunakan Website Sabagai Sarana Penjualan Global Di Produk Qly’s Eyelashes - Kristian Mei Handoko; Agustinus Fritz Wijaya (APTIKOM SUMSEL, 2020)
In this era of globalization, many people use websites as their sales ground. Because it is considered to be able to cover a wider range of sales and if a product already has a web, it will be more trusted and will be more popular in the market, because potential consumers in the present era if they want to buy a product will look for it on the internet first. Is this product famous or not, is this product trusted or not and so on. Furthermore, if people who have products but do not have a website or do not display their products on other websites or social media, then it is certain that these products will be less competitive and not sell well in the market. In this context, I as a researcher want to use Ward and Peppard analysis and SWOT analysis.